Ketogenic diet - a literature review - Iwona Cuber; Artur Aghadi; Edyta Białowąs; Ewelina Dybała; Magdalena Mazurek; Marta Górna (Kazimierz Wielki University, 2023)
Introduction: The ketogenic diet, originally used in the treatment of epilepsy, has recently attracted increasing interest from scientists. There are more and more reports about the possible benefits of using KD. Aim of the study: The aim of the study is to present the assumptions of the ketogenic diet and the effects of its use in weight reduction, treatment of type 2 diabetes and the treatment of cancer and dementia. Description of the state of knowledge: Beneficial effects of the use of a ketogenic diet related to weight reduction and improvement of the lipid profile have been described. The ketogenic diet also allows  to reduce the intake of antidiabetic drugs and reduce or discontinue insulin therapy. Animal studies also suggest benefits of using KD in the treatment of cancer. However, studies involving humans are lacking. There are also reports of the effect of KD on delaying the onset of dementia symptoms. Summary: Despite very promising scientific reports, there are no long-term studies on the impact of the ketogenic diet on cardiovascular risk. Therefore, it should be used after weighing the pros and cons.